Protective and anti-inflammatory effects of caffeic acid phenethyl ester on arsenic-induced vasculitis in vivo - Yasser Kofiah; Eman A.A. Abdallah; Mohamed F. El-Refaei (Phytomedicine Plus)
Vasculitis encompasses a broad spectrum of disorders and has a variety of pathophysiological causes. Purpose: This study aimed to investigate the mechanism by which caffeic acid phenethyl ester (CAPE) protects against arsenic trioxide (AsIII)-induced vasculitis. Materials/methods: Forty male rats were randomly distributed into four groups of 10/group. Group I was kept as the control. Group II was administered CAPE intraperitoneally at 3 mg/kg/day. Group III was intoxicated with AsIII at 10 mg/kg b.wt for 6 consecutive days, while Group IV was intoxicated with AsIII for 6 consecutive days and treated daily with 3 mg/kg b.wt of CAPE intraperitoneally starting from day 1 of intoxication up to 14 days. Results: In the present study, CAPE treatment for 14 consecutive days showed significant improvement in the biochemical markers C-reactive protein, complement-3, complement-4, triacylglycerol, and total cholesterol, as well as the pro-inflammatory cytokines interleukin-1 beta and tumor necrosis factor-alpha. Immunohistochemical examination for proliferating cell nuclear antigen indicated mild immunoreactivity in the aorta cells. Furthermore, histopathological inspection of the aortas revealed significantly less distortion of the wall and fewer rounded nuclei in group IV-treated rats. Conclusion: Overall, the results demonstrated the ability of CAPE to protect against vasculitis and injuries induced by AsIII.